Hukum Islam pada Imple¬mentasi Manajemen Risiko Penyelesaian Pembiayaan Bermasalah Bank Syariah Indonesia (BSI) - Ismail, Yana Chaeru Taufik; Janwari, Yadi; Kamaludin Yusup, Deni; Ahmad Saebani , Beni (Green Publisher Indonesia, 2024)
Islamic banking continues to develop, particularly in product diversification, offering a wider variety of options that have positively impacted the public's willingness to conduct muamalah activities through Islamic banks. Various financing products provide customers with the convenience of selecting options that suit their needs. The object of this research, as explained by Husein Umar in Setiawan Santana, focuses on problematic financing, a condition where significant deviations occur in repayments, leading to delays or potential losses. Problematic financing represents a situation where loan repayment agreements face the risk of failure and tend to lead to potential losses. This study offers new insights by examining the role of Islamic law in managing problematic financing risk at Bank Syariah Indonesia (BSI). The novelty of the research lies in the further exploration of using Islamic contracts (akad) as the main foundation in regulating and resolving problematic financing. Through this approach, the research provides a fresh perspective on how Islamic banks can more effectively manage financing risks while adhering to Sharia principles. The impact of this research on Islamic banking is quite significant. The application of risk management based on Islamic law is expected to enhance public trust in Islamic banking and strengthen its stability in Indonesia. The use of akad as the legal basis in resolving problematic financing ensures transparency and fairness in line with Sharia principles. This provides protection for both customers and the bank, creating a stronger foundation for the sustainability of Islamic banking in the future.